Online health information impacts patients' decisions to seek emergency department care. - Pourmand, Ali; Sikka, Neal (Western Journal of Emergency Medicine: Integrating Emergency Care with Population Health, 2011)
Objective: To investigate the impact of online health information (OHI) and patients' decisions to seek emergency department (ED) care. Methods: We conducted a survey of a convenience sample of 489 ambulatory patients at an academic ED between February and September 2006. The primary measure was the prevalence of Internet use, and the secondary outcome was the impact of OHI on patients' decision to seek ED care. Results: The study group comprised 175 (38%) males. Mean age was 33 years old; 222 (45.4%) patients were white, 189 (38.7%) patients were African American, and 33 (6.7%) were Hispanic. 92.6% had Internet access, and 94.5% used email; 58.7% reported that OHI was easy to locate, while 49.7% felt that it was also easy to understand. Of the subjects who had Internet access, 15.1% (1.6, 95% CI 1.3-2.0) stated that they had changed their decision to seek care in the ED. Conclusion: This study suggests that Internet access in an urban adult ED population may mirror reported Internet use among American adults. Many ED patients report that they are able to access and understand online health information, as well as use it to make decisions about seeking emergency care.